Pengaruh Atribut Produk Dan Pengetahuan Konsumen Terhadap Niat Pembelian Pada PT Hasjrat Abadi Cabang Limboto. - Iyan Ayuba (Universitas Gorontalo, 2018)
Iyan Ayuba, 2018 the effect of knowledge and attributes of products to customer friendly shopping at pt. hasjrat abadi cabang limboto. The purpose of this study was to determine how attributes influence consumer knowledge of the product and purchase intentions in PT Hasjrat Abadi cabang Limboto and the population in this study are all consumers who never make purchases at PT Hasjrat Abadi cabang Limboto. Samples were taken using purposive sampling sample size of 50 people . Data analysis technique used is multiple regression . The results showed that : 1 ) . Product attributes significantly influence purchase intention on PT Hasjrat Abadi cabang Limboto. 2 ) . Consumer knowledge significantly influence purchase intention on PT Hasjrat Abadi cabang Limboto.